Stability analysis with respect to two measures of impulsive systems under structural perturbations - Martynyuk, A.A.; Stavroulakis, I.P. (Український математичний журнал, 1999)
The asymptotic stability with respect to two measures of impulsive systems under structural perturbations is investigated. Conditions of asymptotic (ρ₀, ρ)-stability of the system in terms of the fixed signs of some special matrices are established. Досліджується асимптотична стійкість за двома мірами імпульсних систем при структурних збуреннях. Встановлено умови асимптотичної (ρ₀,ρ)-стійкості системи в термінах знаковизначеності спеціальних матриць.